Variation in Phenolic, Mineral, Dietary Fiber, and Antioxidant Activity across Southern Tunisian Pearl Millet Germplasm. (16th July 2022) - Triki, Tebra; Tlahig, Samir; Benabderrahim, Mohamed Ali; Elfalleh, Walid; Mabrouk, Mahmoud; Bagues, Mohamed; Yahia, Hédi; Belhouchette, Khaled; Guasmi, Ferdaous; Loumerem, Mohamed
Abstract : Pearl millet crop, reputed as one of the most important food sources cultivated in arid and semiarid parts of Africa and Asia, is known to be a source of many bioactive molecules with potential health-promoting properties. In Tunisia, this crop presented historically rich and diversified germplasm, which is being threatened by genetic erosion. The preservation programs of these species have been held for more than 20 years via participatory breeding schemes. A prospection was undertaken to collect pearl millet cultivars preserved in the last two decades from south-eastern Tunisian farmers to estimate their variability and performances. The aim of this study was to assess the profiles of phenolic compounds, antioxidant capacities, mineral composition, and dietary fiber contents of ten pearl millet cultivars in south-eastern Tunisia. The total phenolics and flavonoids in the free fraction ranged from 506.33 to 1287.71 µ g.g −1 DM ferulic acid equivalent (FAE) and 4.17 to 12.53 µ g.g −1 DM catechin equivalent (CE), respectively. The highest polyphenolic content from all genotypes was 1134.96 µ g·g −1 DM (genotype Med.AG1.3). LC-MS analysis of individual phenol compounds allowed the identification of eight phenolic acids in millet grains. The quinic acid, p -coumaric acid, and caffeic acid were predominant phenolic acids, and six flavonoid compounds with cirsiliol and silymarin were the predominant flavonoids. The ranges of mineral contents variation were 693.10 to 1075.40 and 80.75 to 175.40 μ g·g −1 for Ca and Mg, respectively, and 9.55 to 32.80, 0.75 to 8.60, 1.84 to 12.21, and 3.63 to 11.40 μ g·g −1 for Na, Zn, Cu, and Fe, respectively. The content of NDF, ADF, and ADL per dry weight varied from 20 to 31%, 1 to 4.2%, and 0.4 to 2.3%, respectively. Overall, considering the variability among the assessed attributes, heatmap analysis showed the association between each of the traits as related to the clustered genotypes.